The increase sensitivity of PNP-magnetotransistor in CMOS technology - Leepattarapongpan, Chana; Phetchakul, Toempong; Pengpad, Puttapon; Srihapat, Arckom; Jeamsaksiri, Wutthinan; Chaowicharat, Ekalak; Hruanun, Charndet; Poyai, Amporn (My University, 2015)
This paper presents improve sensitivity of pnp-magnetotransistor for detect vertical magnetic field response. The device structure consisted of one emitter, four collectors and four bases. The four collectors are separate to form four terminals. The same is true for the four bases. The experiment showed that, at 2 and 4mA of biasing current, magnetic field in BZ direction sensitivity within the range of 0-400 mT are 0.045 and 0.09 mV/mT in single mode. The sensitivity of merge mode are 0.15 and 0.3 mV/mT. The magnetic field response of merge mode shows 4-time increase of the magnetic field sensitivity comparative to single mode.
Keywords: HALL Effect; Lorentz force; Magnetotransistor